Developing Science Learning Material with Authentic Inquiry Learning Approach to Improve Problem Solving and Scientific Attitude (Jurnal Pendidikan IPA Indonesia, 2017)
This research was conducted to (1) produce science material learning based Authentic Inquiry Learning which is appropriate to improve problem solving and students scientific attitude; (2) know the potency of developing scientific attitude in science learning material based authentic inquiry learning; and (3) know the potency of developing scientific attitude in science learning material based authentic inquiry learning. The research method was Research and Development (R D), by pointing to Four D models and Borg Gall Model. There were 4 main phases (define, design, develop, disseminate) and additional phases (preliminary field testing, main product revision, main field testing, and operational product revision). The instruments used included product validation questionnaire, problem solving test, observation sheet of problem solving, and scientific attitude questionnaire. Result data of validation, problem solving test, scientific attitude questionnaire were analyzed descriptively. The result showed that : (1) science learning material based authentic inquiry learning that was developed was considered as very good by expert lecturers and teachers, and it was appropriate to use in learning process; (2) science learning material based authentic inquiry learning could improve students’ problem solving; (3) science learning material based authentic inquiry learning could improve students’ scientific attitude.